Development of Student Worksheet Discovery Model Based on Video Logger Pro Analysis to Improve Problem-Solving Skills of Physics Teacher Candidates - Dens E. S. I. Asbanu (Jurnal Penelitian Pendidikan IPA, 2023)
Students are less active in learning, lack motivation, textbooks are full of mathematical equations without detailed explanations, and use conventional methods. LKS can be used as an alternative medium to improve problem-solving skills. This study aims to develop pro video logger-based worksheets based on the guided discovery that is valid and effective to improve problem-solving for prospective physics teachers. The research method used is ADDIE. The research subjects were 36 mechanical engineering students. The research instrument used was a validation sheet and a test instrument for problem-solving skills. LKS is feasible to use if it is valid in the category of high validity and reliability, there are significant differences in the pretest and posttest, and the increase in problem-solving skills in the medium N-gain test category is minimal. The results showed that the LKS is valid with an average validity of 0.88 with a high validity category, the value of R = 0.752 > 0.70 means reliable, the Wilcoxon equation. Sig. = 0.000 <0.05, meaning that there is a significant difference pretest and posttest, and the average N-gain = 0.64 in the medium category, minimum and maximum N-gain = 0.087 and 0.640